2003
DOI: 10.1038/sj.gene.6363932
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant HS1 molecule in a patient with systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the activation of autoreactive B lymphocytes, which are supposed to carry aberrant signal transduction after the stimulation of B-cell receptor (BCR). To investigate abnormalities in BCR-mediated signaling pathway in lupus B lymphocytes, we analyzed HS1, a molecule downstream of BCR, in 80 Japanese SLE patients. We identified 37 amino acid deletion of HS1 in a 25-year-old female patient, and the aberrant HS1 lacked a part of a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…These results suggest that this unique insertion-type polymorphism in HS1 accelerates signal transduction through BCR, which probably results in a lowered threshold of BCR triggering and dysregulation of the immune system, leading to the development of SLE. A recent study demonstrated another molecular defect in HS1 that transmits an accelerated signal through BCR in a patient with SLE (24). Taken together, these observations suggest that defects in HS1 function, as well as those in the molecules involved in BCR-mediated signal transduction, might be important factors in the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…These results suggest that this unique insertion-type polymorphism in HS1 accelerates signal transduction through BCR, which probably results in a lowered threshold of BCR triggering and dysregulation of the immune system, leading to the development of SLE. A recent study demonstrated another molecular defect in HS1 that transmits an accelerated signal through BCR in a patient with SLE (24). Taken together, these observations suggest that defects in HS1 function, as well as those in the molecules involved in BCR-mediated signal transduction, might be important factors in the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 83%
“…The N-terminal 37-amino acid repeats can form a helix-turn-helix structure frequently found in the DNA binding domain of various transcription factors. Deletion of one of the 37-amino acid motifs was recently identified in a patient with SLE and was associated with increased apoptosis in WEHI-231 B lymphoma cells transfected with the mutant HS1 and in the patient's peripheral B lymphocytes (24). Because the 37-amino acid repeats are considered to be important in HS1 binding to F-actin (a cytoplasmic protein) in NIH313 cells (39), this mutant HS1 may display reduced binding to F-actin and thereby more easily translocate from cytoplasm to nucleus after BCR stimulation, accelerating signal transduction (40).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations